TINJAUAN KRIMINOLOGI TERHADAP SUAMI PELAKU PENGANIAYAAN DALAM RUMAH TANGGA - Lailatus Sururiyah (Universitas Muhammadiyah Sumatera Utara, 2017)
Persecution is to deliberately injure the human body or cause pain as a goal, not as a means of achieving a permissible purpose, such as hitting a child within the boundaries deemed necessary by the child’s own parent. The persecution of husbands in the household is included in criminology crimes. It is known that many areas in Indonesia where husbands abuse in the household in this case the persecution to his wife and children. It is understood that the causes of husbands are persecuting the household, namely the wife and child in general, because the husband is often drinking and using drugs, but the whole cause is economic, social, psychological, supporting, and also the cause of the accident. The criminology review of husband’s abuse of wife and child when the persecution causes pain, discomfort to the body, the wound of the body. And there must also be elements of the act, either originated from attacks or fights. The consequences of criminal law for husbands who inflict abuse on their wives and children are imposed in accordance with Article 44 of Laws Number 23/2004 on the Elimination of Domestic Violence and also Article 80 of Laws Number 35/2014 on Child Protection.